Peripheral Blood Gene Expression Changes Associated With Primary Graft Dysfunction After Lung Transplantation. Issue 7 (17th February 2017) - Diamond, J. M.; Cantu, E.; Porteous, M. K.; Suzuki, Y.; Meyer, K. C.; Lederer, D. J.; Milewski, R. K.; Arcasoy, S.; D'Ovidio, F.; Bacchetta, M.; Sonett, J. R.; Singh, G.; et al.
Abstract : Recipient responses to primary graft dysfunction (PGD) after lung transplantation may have important implications to the fate of the allograft. We therefore evaluated longitudinal differences in peripheral blood gene expression in subjects with PGD. RNA expression was measured throughout the first transplant year in 106 subjects enrolled in the Clinical Trials in Organ Transplantation‐03 study using a panel of 100 hypothesis‐driven genes. PGD was defined as grade 3 in the first 72 posttransplant hours. Eighteen genes were differentially expressed over the first year based on PGD development, with significant representation from innate and adaptive immunity genes, with most differences identified very early after transplant. Sixteen genes were overexpressed in the blood of patients with PGD compared to those without PGD within 7 days of allograft reperfusion, with most transcripts encoding innate immune/inflammasome‐related proteins, including genes previously associated with PGD. Thirteen genes were underexpressed in patients with PGD compared to those without PGD within 7 days of transplant, highlighted by T cell and adaptive immune regulation genes. Differences in gene expression present within 2 h of reperfusion and persist for days after transplant. Future investigation will focus on the long‐term implications of these gene expression differences on the outcome of the allograft. Abstract : In this multicenter observational cohort study, Diamond et al demonstrate significant early overexpression of innate immune/inflammasome‐related gene expression and underexpression of T cell and adaptive immunity‐related genes in the peripheral blood of lung transplant recipients with primary graft dysfunction.